GURU YANG PROFESIONAL MEMILIKI KECERDASAN INTELEKTUAL, EMOSIONAL DAN SPIRITUAL - Sattu Alang (240-540X)
Intelligence quotient (IQ) is an intelligence that gives the ability to count, analogous, imagination, and have creativity and innovation. Then the emotional intelligence include self-control, passion, and persistence, and the ability to motivate yourself and endure the frustration, the ability to control impulses and emotions, not to over in pleasure, set the mood and keep the load stress does not overwhelm the capacity to think , to read the innermost feelings of others (empathy) and pray, to maintain relationships, the ability to resolve conflicts, and to lead themselves and their surroundings. Furthermore, spiritual intelligence is as intelligence to deal with the issue of meaning or value to put the behavior and life in the context of a broader meaning and rich. Future teacher is a teacher who has the intellectual, emotional and spiritual abilities and skills that can create an optimal learning outcomes, have sensitivity in reading the signs of the times, have intellectual insight and have thinking forward, and never feel satisfied with the knowledge that available to him. When the three intelligence above, we can have and do as a professional teachers.